Root nitrogen concentration of sorghum above 2% produces least Striga hermonthica seed stimulation - Ayongwa, G.; Stomph, T.; Emechebe, A.; Kuyper, T. (Wiley, 2006)
A series of pot and laboratory experiments was carried out to assess the effects of N status of sorghum roots and timing of N application (as NH4NO3) on the germination of Striga hermonthica seeds. Root N concentrations varied from 10 to 26 mg N g−1. The cut root and the root exudates technique used in assaying S. hermonthica seed germination gave similar results. However, the cut root technique was easier to handle and more discriminating at low germination levels. S. hermonthica seed germination per unit sorghum root mass followed a broken-stick model. It decreased with increasing root N concentrations, reaching lowest levels at a root N concentration of 19.5 mg N g−1, after which no further reduction occurred. It was not possible to reduce S. hermonthica seed germination to a zero level. Timing of N application influenced the time a higher N concentration is reached, not the S. hermonthica seed germination. Both timing and rate of N application are important in maintaining root N concentrations above 19.5 mg N g−1, thereby potentially reducing S. hermonthica germination in the field. Translation of results to reductions in infection levels and yield losses is hampered by density-dependent relations after the S. hermonthica germination stage.